The specific study of word forms and how they are affected by their origin is known as _____.
archaeology
morphology
semantics
linguistics

vchutkan|Points 6589|

Question

Asked 1/27/2015 1:24:03 PM

Updated 192 days ago|8/9/2018 7:12:40 PM

1 Answer/Comment

This answer has been confirmed as correct and helpful.

Edited by Masamune [8/9/2018 7:11:51 PM], Confirmed by Masamune [8/9/2018 7:11:54 PM], Masamune [8/9/2018 7:11:54 PM]

Rating

3

Man has developed an extensive vocabulary for communicating. TRUE.

Added 192 days ago|8/9/2018 7:12:40 PM

This answer has been confirmed as correct and helpful.

Which of the following constants can be added to x^2 - 3x to form a perfect square trinomial? User: Solve x^2 - 4x - 7 = 0 by completing the square. What are the solutions?
User: Solve 2x 2 + 8x - 12 = 0 by completing the square. What are the solutions?
**Weegy:** 8x^2 - 2x = 1; 8x^2 - 2x - 1= 0; (4x + 1)(2x - 1) = 0 (4x + 1) = 0; 4x = -1, x = -1/4 or (2x - 1) = 0; 2x = 1; x = 1/2 Solution set: {x = -1/4, x = 1/2} **User:** Which of the following constants can be added to x^2 - 6x to form a perfect square trinomial?
6
9
36 **User:** Solve x^2 + 8x + 8 = 0 by completing the square.
Which equation is used in the process? **User:** What is the value of b^2 - 4ac for the following equation?
5x^2 + 7x = 6
9
81
169 **User:** What is the value of b^2 - 4ac for the following equation?
x(x + 8) = 9
28
64
100 (More)

Question

Updated 2/1/2015 3:47:21 AM

4 Answers/Comments

x^2 - 4x - 7 = 0

(x - 2)^2 - 4 - 7= 0

(x - 2)^2 = 11

x - 2 = ± sqrt of 11

x = ± sqrt of 11 + 2

(x - 2)^2 - 4 - 7= 0

(x - 2)^2 = 11

x - 2 = ± sqrt of 11

x = ± sqrt of 11 + 2

Added 1/25/2015 12:36:17 AM

This answer has been confirmed as correct and helpful.

Confirmed by jeifunk [1/25/2015 12:37:57 AM]

2x^2 + 8x - 12 = 0

2(x + 2)^2 - 8 - 12 = 0

2(x + 2)^2 = 20

(x + 2)^2 = 10

x + 2 = ±sqrt of 10

x = ±sqrt of 10 - 2

2(x + 2)^2 - 8 - 12 = 0

2(x + 2)^2 = 20

(x + 2)^2 = 10

x + 2 = ±sqrt of 10

x = ±sqrt of 10 - 2

Added 1/25/2015 12:37:48 AM

This answer has been confirmed as correct and helpful.

Confirmed by jeifunk [1/25/2015 12:38:43 AM]

Solve x^2 + 8x + 8 = 0 by completing the square. (x + 4)^2 = 8 is used in the process.

x^2 + 8x + 8 = 0

(x + 4)^2 - 16 + 8 = 0

(x + 4)^2 = 8

x^2 + 8x + 8 = 0

(x + 4)^2 - 16 + 8 = 0

(x + 4)^2 = 8

Added 1/25/2015 12:39:26 AM

This answer has been confirmed as correct and helpful.

Confirmed by jeifunk [1/25/2015 5:29:59 AM]

The value of b^2 - 4ac for the following equation x(x + 8) = 9 is 100 .

b^2 - 4ac

= 8^2 - 4*1*(-9)

= 64 + 36

= 100

b^2 - 4ac

= 8^2 - 4*1*(-9)

= 64 + 36

= 100

Added 2/1/2015 3:47:21 AM

This answer has been confirmed as correct and helpful.

Confirmed by jeifunk [2/1/2015 4:27:23 AM]

29,287,762

questions answered

There are no comments.